Influência do espaçamento entre linhas na fenologia, produtividade de biomassa e de grãos em genótipos de milheto pérola - Priesnitz, Rafael (2009)
The objective of this study was to evaluate the influence of spacing between lines in phenology, the yield of biomass and grain cultivars in common and IPA-BULK 1 pearl millet. The experiment was installed at the Experimental Farm Dr. Antônio Carlos Santos Pessoa (Unioeste), located on Guará Line, Marechal Cândido Rondon PR city. The experimental design was randomized blocks in factorial scheme 2x4, with four replications. In the treatments were used two genotypes (Usual IPA and BULK-1), conducted at four spacings (20, 40, 60 e 80cm) in plots of 12m2. It was used as seeding rate of 25 kg ha-1 seeds for all treatments. Sowing was done manually on October 10, 2008. It was avaluated the number of days and number of thermal units needed to reach each developmental stage, and the biomass production and grain. In relation to phenology and the number of thermal units, the cultivar had similar, requiring an average of 90.28 days and 795.40 thermal units to reach physiological maturity. The spacing significantly influenced the production of biomass. It was observed that the biomass production decreased in function of the increase in row spacing. The spacing of 20cm between rows was the, on average, increased production of green mass and dry mass at the stage of grain paste with 50.84 ton ha-1 and 17.60 ton ha-1 respectively, green mass and dry mass at the stage of physiological maturity, with 57.58 ton ha-1 and 22.39 ton ha-1 respectively. There was a significant interaction between the factors cultivar and spacing for the production of dry matter in the physiological maturity and grain production. In general, the cultivars had a good yield of biomass and grain, so it can be grown in the region of Marechal Cândido Rondon PR, it is an important alternative for the soil cover in tillage system and also as the power source of animals feeding